Perinatal Risks of Planned Home Births in the United States. Issue 7 (July 2015) - Grünebaum, Amos; McCullough, Laurence B.; Brent, Robert L.; Arabin, Birgit; Levene, Malcolm I.; Chervenak, Frank A.
Abstract : ABSTRACT: Planned home births by midwives, compared with hospital births, are associated with increased risk of neonatal deaths, neonatal seizures, serious neurological dysfunction, and other adverse neonatal outcomes, according to recent studies. The American College of Obstetricians and Gynecologists (ACOG) recommends home births be cephalic singleton pregnancies between 37 and 41 weeks' gestation, with no prior cesarean deliveries, and recommends these births be attended by certified midwives or physicians. This study investigated perinatal risks associated with planned home births by midwives and compared them with recommendations and clinical criteria from the ACOG and the American Academy of Pediatrics. Birth certificate data from 2010 to 2012 were collected from the National Center for Health Statistics of the US Centers for Disease Control and Prevention, which included information on each of the births in the United States each year. The proportion of births that were high risk, particularly breech, twins, prior cesarean delivery, or late term or postterm were compared between in-hospital and out-of-hospital midwifery-attended births. Three provider groups were compared: certified nurse-midwife (CNM)–attended home births, CNM-attended hospital births, and other midwife-attended home births, and odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. The search found 11, 905, 817 deliveries in the United States between 2010 and 2012, including 85, 318 home births and 736, 070 hospital deliveries attended by CNMs; 29, 178 of the 85, 318 home births were performed by someone other than a midwife and were excluded from the study, leaving 56, 140 planned midwife-attended home births, 19, 263 of which were attended by a CNM and 36, 877 attended by other midwives. For the high-risk conditions examined, each is reported as the rate in out-of-hospital births, and ORs are comparing the risk of home births to in-hospital deliveries with midwives. Of the midwife-attended planned home births, approximately 1 in 156 were twin births (OR, 2.06; 95% CI, 1.84–2.31, as compared with in-hospital deliveries), 1 in 23 were vaginal births after cesarean deliveries (OR, 2.08; 95% CI, 2.0–2.17), 1 in 35 were with breech presentation (OR, 3.19; 95% CI, 2.87–3.56), and 3 in 10 were at a gestation of 41 weeks or longer (OR, 1.71; 95% CI, 1.68–1.74). Thus, each of these higher-risk conditions makes up a larger proportion of births in intended home deliveries as compared with in-hospital births attended by CNMs. In conclusion, the study found that at least 30% of planned home births attended by midwives include the prenatal risks identified by ACOG and the American Academy of Pediatrics as contradictions for planned home births. These risks are associated with adverse birth outcomes. Planned home births attended to by non–American Midwifery Certification Board–certified midwives account for 65.7% of planned home births in the United States.